FLOWS OF PROTEST CONTROL IN SÃO PAULO (2013-2014) - MACIEL,DÉBORA ALVES (2021)
ABSTRACT The article analyzes the dynamics of protest control in São Paulo, from June 2013 to June 2014, focusing on coalitions between actors, arenas and institutional repertoires. We argue that the police crackdown on June 13 in São Paulo encouraged ordinary citizens to join the demonstrations, as well as spurred changes in local and federal government responses to protests and in repressive repertoires of social control.